PENGEMBANGAN ANGKUTAN UMUM DI DAERAH SUBURBAN KOTA SEMARANG BERBASIS SISTEM INFORMASI GEOGRAFI - Ferry Hermawan; Bambang Riyanto; Kami Hari Basuki (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2009)
The growth of Semarang City created residential areas in the pheriperal of the city. The objectives of this study is to analyze the development of public transport based on the geographic information system. The method used is a descriptive method, using isoprice and mobility models. The results show that mobility to the central city is influenced by transportation expenses and potensial amount of people transported.Keywords: Public trasport development, isoprice, and mobility model.